Implementasi Kurikulum Merdeka dalam Pembelajaran IPS di SMP Negeri 2 Praya Barat Daya - Safitri, Lili; Sahabudin, Sahabudin; Suandi, Suandi (Universitas Qamarul Huda Badaruddin, 2023)
This study aims to analyze the implementation of the Independent Curriculum in Social Studies (IPS) learning at SMP Negeri 2 Praya Barat Daya. The focus includes planning, implementation, and evaluation of learning based on the principles of the Independent Curriculum. This research employed a qualitative descriptive method. Data were collected through observations, interviews, and documentation involving Social Studies teachers, students, and the school principal. The findings reveal that teachers have developed learning tools based on differentiation and the Pancasila Student Profile, yet challenges remain in the use of digital media and limited facilities. In terms of classroom practice, learning has become more interactive with an emphasis on collaboration, although student engagement varies. Evaluation has begun to adopt formative assessments but has not been fully optimized. These results emphasize that the Independent Curriculum enhances contextual learning but requires stronger support in terms of facilities, teacher training, and student engagement strategies